Synthesis and characterization of nitrogen-rich polybenzoxazines for energetic applications. (May 2022) - Abdous, Slimane; Derradji, Mehdi; Mehelli, Oussama; Belgacemi, Raouf; Soudjrari, Sarah; Ramdani, Noureddine; Khiari, Karim; Kadi, Mohamed El Amine; Liu, Wenbin
In a vision to develop new synthetic routes for the preparation of energetic materials, two new energetic benzoxazine monomers were synthesized via a two-step Mannich reaction process involving the incorporation of nitrogen–nitrogen bonds and explosophore groups (NO2 ) into the monomer backbone. The molecular structures of the synthesized monomers were confirmed by 1 H NMR, Fourier transform infrared and elemental analysis techniques. The curing behavior and the degradation phenomena were evaluated by differential scanning calorimetry-thermogravimetric analysis analyses. The two monomers showed two distinct exothermic peaks related to the polymerization and degradation phases. The energetic performances were evaluated by determining the heat of combustion and formation using a bomb calorimeter, in an oxygen atmosphere. The results indicated that the 2, 4 dinitrophenylhydrazine–based benzoxazine has better energetic properties than the phenylsemicarbazide-based benzoxazine, and the two developed polymers showed comparable performances with nitrocellulose and glycid azide polymer. Overall, this study has demonstrated that the ease of synthesis of the benzoxazine resins via Mannich reaction can be further extended to the energetic field and further research is undergoing to fully unravel the potential of these exceptional materials.